Analisis Kinerja Penukar Kalor Tipe Shell and Tube untuk Pendinginan Governor - Yogi Nugroho Bakti; Markus (Politeknik Negeri Cilacap, 2020)
One of the elements that affect the reliability and service life of a hydraulic pump is the stability level of oil viscosity as a power successor. The stability level of oil viscosity is affected by changes in temperature. The compression and friction process that the oil receives to move the hydraulic pump will increase the oil temperature so that its viscosity level will decrease. To maintain the performance of the hydraulic pump, the oil temperature must be maintained at room temperature. In the case study at PLTA Ir. H. Djuanda, Lurah Kawi Street No.1 Jatiluhur-West Java, to cool the oil, a shell and tube heat exchanger type JPK 13699068 (single tube) is used. This research was conducted to test whether the heat exchanger is still working properly, the parameter is that the cooled oil exit temperature must be close to room temperature. The effectiveness of the heat exchanger will be tested by comparing the test results with the condition of the heat exchanger without impurity factors. The test was carried out by measuring the temperature of the HX intake oil at 44 0C with a discharge of 0.437 kg/s, and the temperature of the HX inlet water at 28 0C with a discharge of 0.498 kg/s. The results showed that, for the coefficient of U between 110 to 350 W/m2 oC with a water impurity factor of 0.0001 m2 oC/W and an oil impurity factor of 0.0002 m2 oC/W, there was a decrease in effectiveness from an average of 74.5% to 73.7%, and there was an increase in oil temperature out of the heat exchanger from an average of 32.07 oC to an average of 32.21 oC.